2022
DOI: 10.1038/s41598-022-05173-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a roughness parameters for defining surface roughness of prosthetic polyethylene Pe-Lite liner

Abstract: The Biosculptor's CNC milling machine, the Biomill, offered four different surfaces machined on positive models. This study aims to adopt the surface topography method in characterizing the four different surface roughness of polyethylene Pe-Lite liner as a product of the Biomill. Three surface parameters chosen were the arithmetic average (Ra), root mean square roughness (Rq), and ten-point height (Rz). The surface parameters were used to define the four different surfaces (STANDARD, FINE, COARSE, and FAST) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, the roughness parameter Rq (Root Mean Square roughness) showed a statistically significant difference between the sample groups ( p < .05) and is more effective in describing the surface roughness, as it depicts the standard deviation of the surface height distribution by statistical methods. Further, it is also far more sensitive than Ra because it provides the roughness measurement at the microscopic level 34 . It is observed that instead of similar grinding and polishing for all the samples, the samples compacted at lower compaction pressure show a higher Rq value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the roughness parameter Rq (Root Mean Square roughness) showed a statistically significant difference between the sample groups ( p < .05) and is more effective in describing the surface roughness, as it depicts the standard deviation of the surface height distribution by statistical methods. Further, it is also far more sensitive than Ra because it provides the roughness measurement at the microscopic level 34 . It is observed that instead of similar grinding and polishing for all the samples, the samples compacted at lower compaction pressure show a higher Rq value.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it is also far more sensitive than Ra because it provides the roughness measurement at the microscopic level. 34 It is observed that instead of similar grinding and polishing for all the samples, the samples compacted at lower compaction pressure show a higher Rq value. In contrast, the sample compressed at higher compaction pressure shows a relatively lower Rq value.…”
Section: Surface Characterizationmentioning
confidence: 86%
“…The result in Table 2 shows the surface roughness value of Jabon wood after sanding with a 100-grit belt sander (P-100) on different surface types, determined using a portable stylus-type profilometer. The surface roughness of solid materials is generally measured using three parameters: average surface roughness (Ra), root mean square roughness (Rq), and ten-point mean roughness (Rz) [ 39 ]. However, Ra is the most used metric for determining wood surface roughness.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the Ra parameter was employed in this investigation to quantify the surface irregularity of Jabon wood. An approach methodology utilizing Ra values has been implemented in prior studies [ 3 , 4 , 5 , 14 , 15 , 39 , 40 ]. The average roughness (Ra) of a profile is calculated by averaging the individual depths and heights (irregularities) of its arithmetic mean elevation.…”
Section: Resultsmentioning
confidence: 99%
“…Rz, or maximum profile height, measures the vertical distance between the highest peak and the lowest valley over a sampling length. Sa, or arithmetic mean of the absolute values of the surface deviations, is another parameter that represents the average surface roughness and was used in this study [ 46 , 47 ]. Scans will be performed at 10 × magnification and 1024 × 1024 pixels resolution.…”
Section: Methodsmentioning
confidence: 99%